Greasing the wheels of the Worldwide Governance Indicators (WGI) through Smart Governance Matrix (SGM) in controlling corruption - Zamri N.A.B.; Abdullah W.M.T.B.W.; Ahmad N.N.B. (Medwell Journals, 2023)
Corruption is perceived as one of the primary disorders to the development of a proficient government because it is a "symptom that something has gone wrong in the management of the state". Better way to address this issue is through coupling up the effort on controlling corruption with the attention on good governance aspects. There is a need to identify a good governance indicators to measure the quality of governance in combating the issue. The World Bank Institute had published the Worldwide Governance Indicators (WGI) which is the most comprehensive set of governance indicators available publicly. Thus, this study aims to facilitate six indicators of WGI into a new propose research framework named as the Smart Governance Matrix (SGM). SGM outlines six governance models. This study will integrates WGI into SGM in order to establish a contribution towards corruption control initiatives. Medwell Journals, 2015.